Growth of Additive Manufacturing Due to Global Pandemic and its Effect on Supply Chain Management - Drumil Newaskar; Shubham Gandhi; Preet Aligave (International Journal of Engineering and Management Research, 2021)
Additive manufacturing is a revolutionary technology because of its ability to creates objects by adding material layer by layer rather than removing material from a block or by moulding procedure. Additive manufacturing has been around for more than three decades but still, traditional manufacturing is the dominant method for manufacturing. COVID-19 pandemic has been a torment globally and has brought distress and instability to the global economy. Due to this, the manufacturing sectors are badly affected. In this time of crisis, additive manufacturing has played a major role. This paper discusses the upsurge of Additive manufacturing due global COVID-19 pandemic and its worldwide impact on supply chain management.